2011
DOI: 10.1002/cbdv.201000357
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Leaf and Flower Essential Oils of Tunisian Lavandula dentata L. (Lamiaceae)

Abstract: Essential oils of Lavandula dentata, a Tunisian native plant, were isolated from leaves and flowers by hydrodistillation in a Clevenger-type apparatus and characterized by GC-FID and GC/MS analyses. The average essential oil yields, means of five replicates, were higher for the flowers (8.60 mg/g) than for the leaves (6.56 mg/g). A total of 72 compounds were identified, accounting for 98.1 and 97.7% of the total oil composition of the leaves and flowers, respectively. The main essential oil constituents were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…The main compounds identified in L. dentata oil were camphor, fenchone and fenchol (61.43, 24.3 and 2.15%, respectively). Tunisian species (Touati et al 2011) showed 1,8-cineole, camphor, and fenchone as major compounds in agreement with the present results. In contrast, main components in Moroccan species were alpha-pinene, beta-pinene, 1,8-cineole and pincarveol (Imelouane et al, 2010), while Algerian species contained 1,8-cineole, beta-pinene, trans-pinocarveol, linalool and myrtenol (Dob et al, 2005;Bousmaha et al, 2006).…”
Section: Chemical Composition Of Essential Oilssupporting
confidence: 92%
“…The main compounds identified in L. dentata oil were camphor, fenchone and fenchol (61.43, 24.3 and 2.15%, respectively). Tunisian species (Touati et al 2011) showed 1,8-cineole, camphor, and fenchone as major compounds in agreement with the present results. In contrast, main components in Moroccan species were alpha-pinene, beta-pinene, 1,8-cineole and pincarveol (Imelouane et al, 2010), while Algerian species contained 1,8-cineole, beta-pinene, trans-pinocarveol, linalool and myrtenol (Dob et al, 2005;Bousmaha et al, 2006).…”
Section: Chemical Composition Of Essential Oilssupporting
confidence: 92%
“…Studies regarding the chemical composition of the EO from different species of Lamiaceae indicate that they are composed mainly of monoterpenoids (Hussain et al, 2013;Koc et al, 2013;Moro et al, 2011;Touati et al, 2011;Yousefzadeh et al, 2013). This result is not surprising because the well-known biosynthetic processes of terpenoids in plants are genetically controlled, and species classified in the same family often present major compounds of the same class (Lukas et al, 2013;Najafian, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of H. rhododon presented a yield of 1.0%, whereas the aerial parts of H. marifolia had a yield of 2.0% (Gonzáles-Chávez et al, 2011;Von Poser et al, 1996). In general, species classified in the Lamiaceae stand out by presenting high potential for EO production (Mechergui et al, 2010;Monfared and Ghorbanli, 2010;Ozcan et al, 2011;Raina et al, 2013;Saei-Dehkordi et al, 2010;Touati et al, 2011;Zouari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, L . dentata has nine different subtaxa, and two different chemotypes have been found in Tunisia . L .…”
Section: Introductionmentioning
confidence: 99%